The Effect of Natural Resources Materials on Student Understanding About the Potential of The Region in Buton Central District - Sabrina Sabrina; Dede Sugandi; Nandi Nandi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Lack of public understanding of natural resource management causes damage that runs relatively but the impact is cumulative so that it becomes difficult to overcome it. Through geography learning materials, especially material on natural resources, it is able to increase students' understanding of the geographical conditions of their area so that they are able to take advantage of the potential of the local area. The purpose of this study was to analyze the effect of learning geography on students' understanding of the potential of the area in Central Buton Regency. This study uses a descriptive method with a quantitative approach. The sample consisted of 116 students from 5 schools in Central Buton Regency.